Fish 54 seafood feasts - LeFavour, Cree (Chronicle Books, 2013)
Fish celebrates the versatility, healthfulness, and ease of preparation of fish and shellfish in more than 120 delicious recipes. Five chapters are organized by flavor profile, including American, Bistro, Latin, East and South Asian, and North African/Mediterranean. Each recipe is grouped into a set matching a main course of fish or shellfish with a complementary grain, pasta, salad, or vegetable. Fish encompasses all of the best techniques for cooking seafood perfectly, including grilling, roasting, salt-crusting, and wok-braising, and all dishes feature sustainable seafood. These exciting recipes make the most of one of the world's healthiest proteins, demystifying it and suggesting a year's worth of meals for cooks of all skill levels